Habituation does not change running economy in advanced footwear technology - Schwalm, L. C.; Fohrmann, D.; Schaffarczyk, M.; Gronwald, T.; Willwacher, S.; Hollander, K. (International Journal of Sports Physiology and Performance, 2024)
Purpose This study aimed to compare running economy across habituated and nonhabituated advanced footwear technology (AFT) in trained long-distance runners.